Pengaruh Penggunaan Metode Pembelajaran Role Pla ying Dalam Materi IPS di SD Terhadap Keaktifan Belajar Siswa Kelas V - Iin Karlina; Putri Ayuningtias; Vivi Vinara Yuka (Program Studi PGSD Kampus UPI di Serang, 2021)
This study aims to (1) describe the steps effective learning by applying the role-playing learning model, (2) describe the increase in student learning activity in playing the role of economic actors in the role playing model, and (3 describe students' responses to the application of the role-playing learning model. The subjects in this study were class V students, totaling 13 people and teachers who teach in the class. The object of this research is the steps of implementing the role-playing learning model, improving results, and responding students to the application of the role-playing learning model. This research using qualitative research. The method of data collection that used in this study is the method of observation, interview method. The results of this study indicate that from the results of discussions and evaluations of the role-playing activities that have been carried out, students get a very good response to social studies learning. Students are very enthusiastic in doing role playing activities. Although there are some students who have not dared to play their roles, the learning activities went smoothly, and students were actively involved in learning activities.